Distribution of Calling Blue, Fin, and Humpback Whales in the North Pacific - Watkins, William A.; Daher, Mary A.; George, Joseph E.; Haga, Scott (2000)
The seasonal distribution of calling blue whales (Balaenoptera musculus) and fin whales (B. physalus), and singing humpback whales (Megaptera novaeangliae) has been analyzed from acoustic data recorded by U.S. Navy Sound Surveillance System (SOSUS) and other hydrophone arrays in the North Pacific. The data from ten arrays were selected as representative of four Regions along the continental margins, labeled Northwest (NW), Northcentral (NC), Northeast (NE), and Southeast (SE). The call data indicate that there is a substantial population of blue whales scattered over the North Pacific and concentrated during the Fall season in the NW and NC Regions. Blue whale calls are recorded in all seasons, particularly in these NW and NC Regions. Fin whales are found in groups but also in relatively large numbers in all Regions, with most calling in the Winter season and in the NC Region, and calling is absent in most Regions during Summer. Fin whale calling includes "F" calls from individuals heard in all seasons and "J" calls from too many whales to separate, particularly prominent in the winter reproductive season. Humpback singing is recorded most in the NC and SE Regions at the time of their Winter/Spring migration. The distribution of singing humpbacks changed in both the NC and SE Regions between the 1996-1997 and 1998-2000 periods.